KONSELING KELOMPOK BERBASIS TEKNIK SENI EKSPRESIF UNTUK MENURUNKAN GEJALA STRES PADA MAHASISWA KEPERAWATAN DI SHELTER DARURAT COVID-19 - Sekarini, Anindyah; Dinni, Siti Muthia (JIP (Jurnal Intervensi Psikologi), 2024)
Health professionals have played a crucial role in addressing the COVID-19 pandemic. The substantial pressure encountered during their work has led to psychological disturbances and stress among these professionals. This study aims to investigate the impact of group counseling based on expressive art techniques on reducing stress levels among health professionals assigned to COVID-19 shelters in Yogyakarta. The study involved five nursing students exhibiting moderate stress levels, measured using the DASS 42 scale. Employing an experimental design with a one-group pretest-posttest approach, The Wilcoxon test was used to analyze the data and determine differences in stress levels before and after the intervention. The results indicate a significant difference in stress levels pre- and post-intervention, with a Z value of -2.060 and a significance level of p = 0.027 (p<0.05). These findings show that group counseling using expressive art techniques can effectively reduce stress levels among health professionals in COVID-19 shelters.